الموازنات الصوتية في الشعر العربي القديم تمثيلها البلاغي وأداؤها الإيقاعي - بودنة, بلقاسم (جامعة الوادي - university of Eloued, 2022)
يهدف هذا البحث إلى التعريف بالدراسات البلاغية، والإيقاعية التي عاينت المسائل الصوتية، وبينت قيمتها في الشعر العربي، واهتمت بطرائق تجسيد الأداء الصوتي للشعر، حين ربطت بين القيمة التزيينية للأبنية الصوتية، ومدى مساهمتها في تشكيل المعنى الشعري وجمالياته وتأثيره، ودورها في منح الظواهر البلاغية أبعادا أسلوبية، مختمرة في المستوى الصوتي، مثلما حاولت تلك الدراسات في وصف الظاهر الصوتية وما يتولد منها من ترجيعات إيقاعية مهمة، وحددت أشكال التلاقي بين البلاغي والإيقاعي في الشعر انطلاقا من آلية الصوت، ولعل الموازنات الصوتية تجسد تمظهراتها البلاغية والإيقاعية بشكل ملفت للانتباه؛ إذ تنبه الدارسون قديما وحديثا إلى أهمية التكوثر الصوتي في البناء الشعري، وبما ينتجه من أشكال جمالية فنية، لها أبعادها الإبلاغية والتأثيرية. This research aims to introduce the rhetorical and rhythmic studies that examined phonological issues, to show up their value in Arabic poetry, and to care the embodiment methods of the sounds performance of poetry, to linked the relationship between the decorative value of acoustic structure, and their role in poetic meaning, its aesthetics, effect, and how giving rhetorical phenomena stylistic dimensions, through the sounds level. those studies attempted to describe the sound phenomenon and the important rhythmic reversals that result from it. They identified the Similarities of rhetorical and rhythmic in poetry through the sound mechanism. Maybe the Sounds balances embodying clearly their rhetorical and rhythmic appearances. The researchers pay attention in the past and present for the importance of Sounds accumulation in poetic constructre, and the artistic, aesthetic forms that it produces, which have communicative and influencer dimensions.
مقال
Keywords: الموازنات الصوتية ، البلاغة، الإيقاع، الشعر، الأداء.; sounds balances , rhetoric, rhythm, poetry, performance